Studi Terapan Konsep Metabolisme dan Simbiosis pada Bangunan Karya Kisho Kurokawa - Mikha Adriani Widagdo; Yusita Kusumarini; lucky basuki (Intra, 2013)
Kisho Kurokawa is a Japanese architect who also founder of metabolism movement. Metabolism movement is the response of over population in 1960s, after World War II. A group of young Japanese architects and designers think this is a problem that have be solved, that’s why they propose metabolism as a new urbanism. Metabolism comes from biological words “metabolism” which is means a chemical process to continue life. They adapt this life principal to create metabolism theory. Metabolism application on architect is in the building flexibility to be able to add or remove as the user’s need. As time goes by, each architect and designer goes their own ways to develop metabolism. Kisho Kurokawa uses life principal and develops metabolism theory to symbiosis. His symbiosis is symbiosis between interior and exterior, symbiosis between cultures or symbiosis between human and nature. Metabolism and symbiosis are his basic concept for his every building design, regardless his modern style with Japanese unsure on it.